2003
DOI: 10.1016/s0012-821x(03)00144-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 830 years of seismic quiescence from palaeoseismology, archaeoseismology and historical seismicity along the Dead Sea fault in Syria

Abstract: The long historical records of earthquakes, the physical effects on ancient building structures and the palaeoseismology provide a unique opportunity for an interdisciplinary tectonic analysis along a major plate boundary and a realistic evaluation of the seismic hazard assessment in the Middle East. We demonstrate with micro-topographic surveys and trenching that the Dead Sea Fault (DSF) offsets left-laterally by 13.6 0.2 m a repeatedly fractured ancient Roman aqueduct (older than AD 70 and younger than AD 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 26 publications
(22 reference statements)
11
132
0
2
Order By: Relevance
“…This range of slip rates is consistent with results from field studies along the DSFS [1][2][3]14]. There is a general agreement that movement on the DSFS has comprised two distinct episodes, although there are debates about the precise timing [9,15,16].…”
Section: Tectonic Settingsupporting
confidence: 81%
See 1 more Smart Citation
“…This range of slip rates is consistent with results from field studies along the DSFS [1][2][3]14]. There is a general agreement that movement on the DSFS has comprised two distinct episodes, although there are debates about the precise timing [9,15,16].…”
Section: Tectonic Settingsupporting
confidence: 81%
“…Recent plate tectonic models have begun to suggest that the northern portion of this transform may be characterized as transpressional in nature. Recent studies have identified clear evidence of active tectonism along the DSFS, including paleoseismic indicators, for the main fault branches along the northern 500 km of the DSFS (i.e., north of approximately 32.5° N) [1][2][3][4][5]. Results of these studies firmly refute recent assertions that the northern DSFS and the strike-slip faults in the Bekaa Valley are presently inactive [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…Johnson and Segall (2004) also extended the Savage and Prescott (1978) model to include the localized creep on a linear viscous shear zone within the upper elastic layer. Geographic distribution of the 15 strike-slip faults considered in this study: (1) Alpine, (2) Altyn Tagh, (3) Dead Sea, (4) Elsinore, (5) Fairweather, (6) Garlock, (7) Karakoram, (8) SAF-Mojave, (9) North Anatolian, (10) Owens Valley, (11) Philippine, (12) SAF-Carrizo, (13) SAF-Indio, (14) San Jacinto, and (15) Haiyuan (Sharp, 1967(Sharp, , 1981Savage and Burford, 1973;Plafker et al, 1978;Sieh and Jahns, 1984;Lubetkin and Clark, 1988;Rockwell et al, 1990;Barrier et al, 1991;Lisowski et al, 1991;Merifield et al, 1991;McGill and Sieh, 1993;Beanland and Clark, 1994;Duquesnoy et al, 1994;Petersen and Wesnousky, 1994;Bennett et al, 1996Bennett et al, , 1997Armijo et al, 1999;Beavan et al, 1999;Lasserre et al, 1999;Bendick et al, 2000;Klinger et al, 2000;Reilinger et al, 2000;Argus and Gordon, 2001;Lee et al, 2001;Miller et al, 2001;Niemi et al, 2001;Norris and Cooper, 2001;Banerjee and BĂŒrgmann, 2002;Brown et al, 2002;Hubert-Ferrari et al, 2002;Fletcher and Freymueller, 2003;Meghraoui et al, 2003;Lacassin et al, 2004;…”
Section: Constraining Time-dependent Earthquake-cycle Modelsmentioning
confidence: 99%
“…However, the analysis of the structural displacement has been proved controversial (Westaway, 2004;Mart et al, 2005). The estimated slip rate varies between 1 and 10 mm/a following different measurement techniques (field studies, GPS, e.g., Garfunkel et al, 1981;Klinger et al, 2000;Gomez et al, 2003;Pe'eri et al, 2002;Meghraoui et al, 2003).…”
Section: Regional Tectonic Settingmentioning
confidence: 99%
“…Previous structural studies which took place along several fault branches of the DST, such as the Arava fault (AF; e.g., Klinger et al, 2000;Diabat et al, 2004); the Serghaya fault (SF; e.g., Gomez et al, 2001;Gomez et al, 2003) and the Ghab (or Masyaf) fault (GF; e.g., Meghraoui et al, 2003;Chorowitz et al, 2005) suggest notable variations in the amount of displacement and the level of seismicity. Therefore, the question arises to what extent fault-related observations based on geophysical and geological investigations of individual fault segments are valid for large-scale strike-slip faults systems as a whole.…”
mentioning
confidence: 99%